Are serum gamma-glutamyl transferase, high-sensitivity C-reactive protein, and ischaemia-modified albumin useful in diagnosing PCOS?. (2nd October 2016) - Ozturk, Mustafa; Keskin, Ugur; Ozturk, Ozlem; Ulubay, Mustafa; Alanbay, İbrahim and Aydin, Aytekin and Yenen, Müfit Cemal
Abstract: We assessed the serum levels of gamma-glutamyl transferase (GGT), high-sensitivity C-reactive protein (hsCRP) and ischaemia-modified albumin (IMA) in patients with polycystic ovary syndrome (PCOS). Fifty-three patients with PCOS were included in our study along with 40 women with no PCOS as the control group. The patients were divided according to their body mass index (BMI). GGT levels were significantly higher in the women with PCOS than the women in the control group ( p < 0.05). They were also significantly higher in the PCOS women who were normoweight and overweight than the normoweight and overweight women in the control group ( p < 0.001). There was no significant difference in the circulating levels of hsCRP and IMA between the women with PCOS and the controls or between the normoweight and overweight subgroups. GGT may be associated with the diagnosis of PCOS when the threshold is set at >15.5 U/L. With the application of this threshold, raised GGT levels had 83% sensitivity (95% CI 0.70–0.90) and 67.5% specificity (95% CI 0.52–0.79), for the diagnosis of PCOS. In our study, GGT levels were elevated in the PCOS patients independent of BMI and could thus be an important marker of PCOS.